PSYCHOLOGY IN YASHPAL'S NOVELS: यषपाल के उपन्यासों में मनोवैज्ञानिकता - K.P., Ushakumari (International Journal of Research -GRANTHAALAYAH, 2021)
English: Yashpal's literature is an expression of revolutionary sentiments and ideas. His literature is placed on the ground of reality, in which the struggle of generations and the interruption of social life is highlighted. Being a true Marxist litterateur, he is an advocate of the "Art for Life". He successfully ran his pen in all the disciplines of literature such as story, novel, montage, travelogue, translation, essay. Yashpal is the second revolutionary novelist after Premchand. His major novels are 'Dada Comrade', 'Deshadrohi', 'Divya', 'Party Comrade', 'Man's Form', 'Anita', 'Jhutha-Sach', 'Twelve Hours' and 'Why How'? . Hindi: यषपाल का साहित्य क्रांतिकारी भावों और विचारों का अभिव्यक्त रूप है । उनका साहित्य यथार्थ की धरती पर रखा गया है, जिसमें पीढ़ियों का संघर्ष और सामाजिक जीवन का अन्तर्द्धन्द्ध मुखरित है । एक सषक्त माक्र्सवादी साहित्यकार होने के नाते वे ‘‘कला जीवनके लिए” मत के समर्थक हैं । उन्होनें साहित्य की सभी विधाओं जैसे कहानी, उपन्यास, एकांकी, यात्रावर्णन, अनुवाद, निबन्ध में अपनी कलम सफलतापूर्वक चलायी । प्रेमचन्द के उपरांत यषपाल ही दूसरे क्रांतिकारी उपन्यासकार हैं। ‘दादा कामरेड’, ’देषद्रोही’, ’दिव्या’, ‘पार्टी कामरेड’, ‘मनुष्य के रूप’, ‘अनिता’, ‘झुठा-सच’, ‘बारह घंटे’ तथा ‘क्यों कैसे’?, आदि उनके प्रमुख उपन्यास हैं ।